The supervisory authority in the Mamluk state on the textile industries 648-923 AH / 1250-1517 AD - طالب, مران; محسن يونس ,; أحمد الحميد العنزي, (Latakia University Journal - Arts and Humanities Sciences Series, 2023)
This study deals with textile industries of all kinds in both the Levant and Egypt, and the role of the regulatory body of the Mamluk Sultanate in controlling these crafts and industries that were providing the Mamluk community with everything it needed in terms of clothing and other textiles. Linen, wool and silk, the places where they were grown in the Levant and Egypt, their types and stages through which these primary raw materials went through in the manufacturing process, the conditions imposed by the Mamluk state on the owners of these industries and crafts, as well as the appointment of the Mamluk administration to specialized employees whose task is to monitor these industries, as the means and methods of fraud abounded followed in the work of these crafts, which necessitated the imposition of strict control over them, and perhaps the administrative apparatus established by the Mamluk Sultanate had an important role in maintaining the continuity of the quality of services provided to members of society, through the conditions that it set and sought to implement, so attention, follow-up, control and punishment, Its results have resulted in preventing the manipulation, fraud and fraud of the owners of industries and crafts in order to achieve large profits.